2021
DOI: 10.1089/tmj.2021.0111
|View full text |Cite
|
Sign up to set email alerts
|

Patient Satisfaction with Telehealth During COVID-19: Experience in a Rural County on the United States–Mexico Border

Abstract: Background: The aim of this study was to analyze patient satisfaction with telehealth in a rural county on the United States-Mexico border after rapid expansion of telehealth services during the COVID-19 pandemic. Materials and Methods: Chiricahua Community Health Centers, Inc., a federally qualified health center in southeastern Arizona, conducted phone surveys with 562 patients to measure various outcomes related to patient satisfaction and experience with telehealth between June and August 2020. Data from p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 21 publications
4
15
0
Order By: Relevance
“…Our findings align with previous research that found high rates of satisfaction with telemedicine in other settings [ 17 , 19 , 20 ], as well as preferences for in-person relationships with clinicians [ 16 ]. They build upon prior literature that has demonstrated high initial interest in and perceived effectiveness of video visits and other digital healthcare modalities among racially/ethnically and/or linguistically diverse patients, including Spanish-speaking patients from our same healthcare delivery system [ 12 , 21 , 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…Our findings align with previous research that found high rates of satisfaction with telemedicine in other settings [ 17 , 19 , 20 ], as well as preferences for in-person relationships with clinicians [ 16 ]. They build upon prior literature that has demonstrated high initial interest in and perceived effectiveness of video visits and other digital healthcare modalities among racially/ethnically and/or linguistically diverse patients, including Spanish-speaking patients from our same healthcare delivery system [ 12 , 21 , 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…Our findings match the results shown by Kaur et Al., who showed that respondents expressed 84-100% agreement to telemedicine health service provided for management of hyperthyroidism [16]. Similarly other researchers also have shown high satisfaction of patients who used telemedicine health service during pandemic [17][18][19].…”
Section: Discussionmentioning
confidence: 80%
“…Prior surveys have found that patients were generally satisfied with telemedicine. [18][19][20][21][22][23][26][27][28] A qualitative study found that while safetynet patients in San Francisco were highly satisfied with their telemedicine visits, they generally preferred in-person visits. 31 Consistent with these findings, our qualitative study indicated broad support for having the option of home-based synchronous telemedicine visits in primary and behavioral health care.…”
Section: Discussionmentioning
confidence: 99%
“…Despite robust literature on telemedicine, studies specifically focused on patients' perspectives on telemedicine visits in primary care [12][13][14] and behavioral health care [15][16][17] are fairly limited and often focused on highly selected populations (e.g., veterans with access issues). 14,17 Furthermore, while the literature on patient experiences of telemedicine has grown since the onset of the COVID-19 pandemic, most of the studies assessing patient perspectives have used brief surveys that assessed only overall satisfaction, [18][19][20][21][22][23][24][25][26][27][28][29] and none has included perspectives on telemedicine modality (video vs. telephone). Understanding and incorporating patients' nuanced perspectives is a key aspect of providing patient-centered care, identified by the Institute of Medicine (IOM) as one of six key elements of high-quality care.…”
Section: Introductionmentioning
confidence: 99%